The electrochemical response of core-functionalized naphthalene Diimides (NDI) – a combined computational and experimental investigation. (20th January 2021) - Wiberg, Cedrik; Busch, Michael; Evenäs, Lars; Ahlberg, Elisabet
Highlights: Electrochemical parameters of nine naphthalene diimides are acquired using DFT. Cyclic voltammograms are simulated based on DFT predictions. Structure-property relations are established. Experimental results are in qualitative agreement with simulated cyclic. pKa values of a 2, 6-di(dimethylamino)-naphthalene diimide are acquired by 1 H NMR. Abstract: Aqueous organic redox flow batteries (AORFBs) have attracted increased interest as sustainable energy storage devices due to the desire of increasing electricity production from renewable energy sources. Several organic systems have been tested as redox active systems in AORFBs but few fundamental electrochemical studies exist. This article provides reduction potentials and acid constants, pKa, of nine different core-substituted naphthalene diimides (NDI), calculated using density functional theory (DFT). Reduction potentials were acquired at each oxidation state for the nine species and were used to achieve a correlation between the electron donating ability of the substituents and the potential. Cyclic voltammograms were simulated using the scheme-of-squares framework to include both electron and proton transfer processes. The results show that the anion radical is unprotonated in the entire pH range, while the dianion can be protonated in one or two steps depending on the substituent. The core substituents may also have acid-base properties. and optimization of the redox properties for battery applications can therefore be obtained both by changing the core substituent and by changing pH of the electrolyte. Three core-substituted NDI molecules were studied experimentally and good qualitative agreement with the theoretically predicted behaviour was demonstrated. For 2, 6-di(dimethylamino)-naphthalene diimide (2DMA-NDI), the calculations showed that one of the DMA substituents could be protonated in the accessible pH range and pKa was determined to 3.95 using 1 H NMR spectroscopy. The redox mechanism of each molecule was explored and the qualitative agreement between theory and experiment clearly shows that this combination provides a better understanding of the systems and offers opportunities for further developments. The applicability of NDI for redox flow batteries is finally discussed. Graphical abstract: The electrochemical redox mechanisms for several naphthalene diimides are evaluated using density functional theory and cyclic voltammetry simulations combined with experimental electrochemistry. Image, graphical abstract